CLIL-BASED MULTISENSORY INTENSIVE READING IN AN ESP PROGRAM - Sukisno, Sukisno; Lustyantie, Ninuk; Chaeruman, Uwes Anis (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to investigate the integration of a multisensory approach within a Content and Language Integrated Learning (CLIL) framework to enhance intensive reading skills among English for Specific Purposes (ESP) students. The theory of multisensory learning, which emphasizes engaging multiple learning modalities, informs the study. Data were collected from 25 pharmacy students at Universitas Muhammadiyah Kuningan, Indonesia. A qualitative case study design employed classroom observations, student interviews, and feedback surveys to evaluate the effectiveness of CLIL-based multisensory techniques. Thematic analysis was utilized to identify patterns and recurring themes in the collected data, providing insights into students’ experiences and outcomes. Results indicate significant improvements in students’ reading comprehension and engagement levels post-intervention. Using multimedia applications and interactive activities allowed for a richer learning experience and supported diverse learning styles. However, challenges related to unfamiliar technology usage highlighted the necessity for additional training for both students and instructors. The finding underscores the potential of combining multisensory learning with CLIL in ESP contexts, while also emphasizing the importance of professional development for educators to optimize teaching strategies. Future studies are recommended to explore the long-term impact of multisensory approaches on other language skills and their applicability in various educational settings.